Selection of powdery mildew resistant and susceptible grapevine genotypes with molecular markers - Molnár, Stella; Galbács, Zsuzsanna; Halász, Gábor; Hoffmann, Sarolta; Veres, Anikó; Szőke, Antal; Galli, Zsolt; Szádeczky-Kardoss, Bence; Kozma, Pál; Kiss, Erzsébet; Heszky, László (Acta Agraria Debreceniensis, 2007)
Incorporation of competitive quality and resistance against the most important fungal diseases (powdery and downy mildew) in a cultivar is one of the most important aims of grapevine breeding. In the 20th century, the most advanced results in grapevine resistance breeding were achieved by French researchers. They used resistant cultivars in more than 30% of their growing areas. In these varieties, North American wild Vitis species were the resistance gene sources. The discovery of immunity-like resistance of Muscadinia rotundifolia opened new perspectives in resistance breeding. M. rotundifolia harbours a dominant powdery mildew gene, providing resistance in highquality cultivars after back-crosses with V. vinifera varieties. M. rotundifolia has been involved in the Hungarian grape breeding programs since 1996, thanks to a French-Hungarian variety exchange. In addition to traditional selection methods, application of MAS (Marker Assisted Selection) based on various types of molecular markers, can provide additional tools for these efforts. Run1 locus, responsible for powdery mildew resistance, was identified in Muscadinia rotundifolia. Molecular markers closely linked to this locus are very significant in screening progenies deriving from M. rotundifolia and V. vinifera crosses, making possible the discrimination between resistant and susceptible genotypes at DNA level. In our analyses BC5 progeny of (M. rotundifola×V. vinifera) BC4×Cardinal (V. vinifera) tested for powdery symptoms were analysed with PCR-RFLP (GLP1- 12P1P3) and microsatellite markers (VMC4f3.1, VMC8g9). Our results proved the applicability of the linked markers and reliability of marker assisted selection.